MENINGKATKAN HASIL BELAJAR PENJASORKES DALAM PEMBELAJARAN NARKOBA MELALUI MEDIA AUDIO VISUAL PADA SISWA KELAS X MIPA-2 SMA NEGERI 1 SIGLI - Yusnaidi Yusnaidi (Jurnal Sains Riset, 2022)
Drugs are one of the materials taught in high school (SMA) as an early effort for students to fall into the dangers of drugs, especially among teenagers at this time and in the future. However, in reality the learning process has not been carried out optimally because students are less clear in receiving material from the teacher, so students have difficulty understanding the material. This affects student learning outcomes, it is necessary to have media learning aids as a means of supporting student learning. The problem in this study is "Can learning about drugs using audiovisual media improve student learning outcomes for class X MIPA-2 SMA Negeri 1 Sigli, Pidie Regency in the 2021/2022 academic year?". The purpose of this study was to determine the effectiveness of using audio-visual media in improving student learning outcomes. This research is classroom action research which consists of two cycles. Each cycle consists of 4 stages, namely planning, action, observation and reflection. Data collection was carried out using field observations made by evaluators and student questionnaires. The data obtained will be analyzed with the existing formula by the evaluation of the collaborator, namely the physical education teacher and the researcher. Affective observation data in the first cycle reached 59.27% (enough) in the second cycle, it increased to 89.14% (good), after being analyzed it increased by 29.87%. From the results of student mastery in the first cycle reached 48.57% in the second cycle, it increased to 100%, after being analyzed there was an increase of 51.43% while the class average value in the first cycle was 67.57 and in the second cycle 86.71. Based on the results of the research above, it is concluded that learning using audio-visual media can improve student learning outcomes. Therefore, it is expected that physical education teachers at SMA Negeri 1 Sigli can use audio-visual media in learning about drugs. Learning using audio visual media can also be used as an alternative teaching system so that the learning atmosphere is always fun according to the objectives of PAIKEM learning.Keywords: Learning Drugs Learning Media, Audio Visual, Learning Outcomes